Efeitos do desalinhamento da taxa real de câmbio sobre o crescimento econômico, 2001-2014 - Kamenach, Kerssia Preda (2019)
There is an important empirical literature that tries to demonstrate the misalignment of the real rate of exchange effects on economic growth. This literature is divided into at least two main approaches: the first, inspired by the Washington Consensus literature, argues that misalignment of the real exchange rate is prejudicial to economic growth, while the second admits that the undervaluation of the real exchange rate favors product expansion. Rodrik’s studies (2008) are one of main references of this approach. In this context, this dissertation advances in the literature when presenting new econometric evidences for this relation, contemplating a sample of sixty-five developing countries and thirty-one developed countries, observed in the period of 2001 to 2014. A control variables in the growth model is the economic complexity index (ECI), understood as a possible proxy for the level of echnological development, since as the same is more present in the tradable sector goods than in the nontradable goods. In methodological terms, the panel data model with fixed effects was used. The results of the model proposed indicate that the real exchange rate misalignment index coefficient is positive and significant, thus providing empirical support for the hypothesis that the maintenance of an undervalued real exchange rate tends to have a positive impact on economic growth.